The Mediating Role of Risk Perception in the Association between Climate Change Awareness and Mitigation Effort on Riau Haze - Hidayati, Nurul; Hanifah, Jilan; Aiyuda, Nurul; Yunas, Indri Meilani (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: The purpose of this study is to see whether risk perception can mediate the relationship between climate change awareness and adaptive haze mitigation efforts in Pekanbaru.Methodology: The subjects in this study were Pekanbaru people who were directly affected by the haze and had lived in Pekanbaru. Subjects in this study were 168 (47 men and 121 women). With an average age of 23.27 years. This study uses three scales. First, the smoke haze mitigation scale, second, the haze risk perception scale, and the third scale, the climate change awareness adaptation scale.Results: The results showed that Risk Perception can mediate Climate Change Awareness with smoke haze mitigation efforts in Pekanbaru (B = .4158 p = .000).Applications / Originality / Value: This study shows the correlation between the value of risk perception, the value of mitigation, and the value of climate change awareness. This study shows that risk perception can mediate the relationship between climate change awareness and mitigation. This study has implications for smoke haze mitigation efforts in Pekanbaru both by individuals, institutions and the government.